URGENSI KEBIJAKAN PEMEKARAN DAERAH OTONOM BARU ACEH MALAKA - Wilda Umami; Ferizaldi Ferizaldi (Sekolah Tinggi Ilmu Administrasi Nasional, 2022)
As a candidate for the new autonomous region for the division of North Aceh Regency, Aceh Malacca has been voiced by community leaders in the western province of North Aceh since 2004. The research objective was to determine and analyze the background that underlies the emergence of the idea of ​​the expansion of the Aceh Malacca district and the urgency of the policy for the expansion of the Malacca Regency area. Findings of this qualitative study could be reported that the background that underlies the emergence of the idea of ​​the expansion of the Aceh Malacca district includes aspects of the political dimension, administrative or technical dimension, and the dimensions of the regional disparity aspect. The urgency of the policy for the expansion of the Malacca Regency area is for the context of improving and accelerating public services, including maximizing public benefits, time efficiency in managing all administrative needs, and regional independence in managing its regional potential. It is recommended that the Central Government reopen the moratorium on expansion so that the Aceh Malacca District can be realized to improve welfare and public services in the region.